Understanding disability : from theory to practice - Oliver, Michael (Palgrave Macmillan, 2009)
"In this long awaited new edition Oliver draws on his own experiences to paint a vivid picture of both the practical challenges of disablement and the theoretical understandings of disability. This approachable text is core reading for social work, nursing, health and social care and social science students taking modules in disability"--Provided by publisher.